Global Microbiota‐Dependent Histone Acetylation Patterns Are Irreversible and Independent of Short Chain Fatty Acids. Issue 6 (26th July 2021) - Saiman, Yedidya; Shen, Ting‐Chin David; Lund, Peder J.; Gershuni, Victoria M.; Jang, Cholsoon; Patel, Shivali; Jung, Sunhee; Furth, Emma E.; Friedman, Elliot S.; Chau, Lillian; Garcia, Benjamin A.; Wu, Gary D.
Abstract : Background and Aims: Although germ‐free mice are an indispensable tool in studying the gut microbiome and its effects on host physiology, they are phenotypically different than their conventional counterparts. While antibiotic‐mediated microbiota depletion in conventional mice leads to physiologic alterations that often mimic the germ‐free state, the degree to which the effects of microbial colonization on the host are reversible is unclear. The gut microbiota produce abundant short chain fatty acids (SCFAs), and previous studies have demonstrated a link between microbial‐derived SCFAs and global hepatic histone acetylation in germ‐free mice. Approach and Results: We demonstrate that global hepatic histone acetylation states measured by mass spectrometry remained largely unchanged despite loss of luminal and portal vein SCFAs after antibiotic‐mediated microbiota depletion. In contrast to stable hepatic histone acetylation states, we see robust hepatic transcriptomic alterations after microbiota depletion. Additionally, neither dietary supplementation with supraphysiologic levels of SCFA nor the induction of hepatocyte proliferation in the absence of microbiota‐derived SCFAs led to alterations in global hepatic histone acetylation. Conclusions: These results suggest that microbiota‐dependent landscaping of the hepatic epigenome through global histone acetylation is static in nature, while the hepatic transcriptome is responsive to alterations in the gut microbiota.